Factors influencing people's ability to maintain their activity levels during treatment for soft tissue sarcoma – A qualitative study. (2nd August 2020) - Dewhurst, Sarah; Tigue, Ruth; Sandsund, Cathy; Mein, Gill; Shaw, Clare
ABSTRACT: Background and Purpose: Soft tissue sarcoma (STS) is a rare connective tissue cancer treated with chemotherapy in the advanced stages. Emerging evidence suggests that physical activity (PA) improves symptom management and quality of life for people undergoing chemotherapy for advanced cancer. However, little research reports their perspective. Method: Semi-structured interviews were used within a phenomenological approach to explore factors that affect people's ability to be physically active while undergoing treatment. Six participants were recruited with purposive sampling. Thematic analysis was used to analyze the data. Results: Three themes identified that PA was seen as an indicator of a persons' own sense of normality; a feeling of loss and uncertainty for the future had impacts on peoples' ability to be physically active, and finally, participants found it challenging to recognize their support needs as their activity levels reduced. Motivation to remain active was individual, and numerous barriers affected participants' ability to remain active as their disease advanced; this included a lack of specific guidance while undergoing chemotherapy. Participants expressed uncertainty generally in identifying and expressing their support needs as they faced multiple complex issues. Conclusion: Health professionals should be proactive in exploring possibilities for PA to mitigate the expected physical decline, and support symptom management while undergoing palliative chemotherapy.